In Hospital outcome of Prediction of Peripheral Arterial disease In Diabetic Tobacco User Patients (Anwer Khan Modern Medical College Journal, 2018)
Background: Peripheral artery disease (PAD) is a distinct atherosclerotic disorder marked by stenosis of the arteries common in tobacco users. Here we investigate prediction of unknown peripheral arterial disease (PAD) amongst patients with diabetic tobacco user and diabetic without tobacco user.Methodology: This prospective observational study was conducted in the Department of Cardiology, Ibrahim Cardiac Hospital and Research Institute, Dhaka, Bangladesh. A total of 60 patients were enrolled in this study who were presented with chest pain associated with lower limb claudication. They were diabetic population, constituted tobacco user in group-I and without tobacco user in group-II.Results: Hypertension was the leading risk factor in both groups (76.7% vs. 80%). 80% of patients of group I and 46.7% of patients of group II had mild form of ABI value. 3.3% of patient of group II had severe form of ABI value. There was no statistical significant difference between two group of patients (p=0.053). 93.3% patients of group I and 96.7% patients of group II had coronary artery disease. Twenty three patients of tobacco user group (n=30) had peripheral artery disease, whereas ten patients of without tobacco user group (n=30) had peripheral artery disease which was statistically significant (p=0.003). Three quarters (76.7%) of group I developed PVD as compared to 33.3% of group II. The risk of developing PVD in diabetic smokers was observed to be more than 6 fold (95% CI: 2.109-20.479) higher than that in non tobacco user were diabetics. 16.7% patients of group I atherosclerosis in femoral artery and the value is 10% in case of group-II, which is statistically in significant(p=0.433).Conclusion: The awareness and implementation of ABI in general clinical practice is poor. A simple, inexpensive test like ABI can improve the diagnosis of PAD in clinical practice and thus help in preventing CAD and consequent death by a range of medical therapies.Anwer Khan Modern Medical College Journal Vol. 9, No. 2: Jul 2018, P 102-109